The Imbalance of FOXP3/GATA3 in Regulatory T Cells from the Peripheral Blood of Asthmatic Patients - Tiantian Chen; Xiaoxia Hou; Yingmeng Ni; Wei Du; Huize Han; Youchao Yu; Guochao Shi (Journal of Immunology Research)
Background. Treg cells play an important role in the pathogenic progress of asthma. Objective. To address the alterations of Treg cells in asthma. Methods. Proliferation-and function-associated markers of Treg cells along with the percentage of Treg cells producing some cytokine from asthmatics and healthy subjects were analyzed by flow cytometry. Besides, the expressions of USP21 and PIM2 in Treg cells were measured by cell immunochemistry after Treg cells were sorted. Results. Treg cells from asthmatic patients showed lower proliferation activity and were more likely to be apoptotic. These cells expressed lower levels of GITR, CTLA-4, Nrp-1, and IL-10 compared to those from the healthy control. Th2-like Treg cells increased in asthmatic patients, while the percentage of IFN-r+ Treg cells was similar between two groups. Moreover, the percentage of IL-4+ Treg cells is related to the asthma control. Treg cells from asthmatic patients expressed more FOXP3 as well as GATA3; the expression level of GATA3 negatively correlated with FEV1%pred. Increased expressions of USP21 and PIM2 in Treg cells from asthmatic patients were found. Conclusion. Treg cells decreased in asthmatic patients, with an impaired immunosupression function and a Th2-like phenotype, which may be due to overexpression of GATA3 and FOXP3, regulated by USP21 and PIM2, respectively.